The Anatomy of Historical Knowledge - Mandelbaum, Maurice (Johns Hopkins University Press, 2019)
Originally published in 1977. In this major work, an overview of the structure of historical writing, Maurice Mandelbaum clarifies some of the problems concerning the nature of history as a discipline, of what constitutes explanation in history, and whether historical knowledge is as reliable as other forms of knowledge. The work is divided into three parts. The first part provides an analytic account of different types of historical inquiry. The second treats at length the nature of causal explanation in everyday life and in science and considers the relation between causes and laws. The final part analyzes the concept of objectivity and estimates both the extent to which the inquiries of historians can be said to be objective and the limits of that objectivity in some types of historical accounts.